Relative fibular strength and locomotor behavior in KNM-WT 15000 and OH 35. Issue 131 (June 2019) - Marchi, D.; Harper, C.M.; Chirchir, H.; Ruff, C.B.
Abstract: Relative fibular/tibial strength has been demonstrated to vary with locomotor behavior among anthropoid primates. In this study fibular/tibial strength was determined in KNM-WT 15000, a juvenile Homo erectus individual (1.5 Ma), and in OH 35, a Homo habilis (or possibly Paranthropus boisei ) individual (1.8 Ma), and compared to that of adult modern humans (n = 79), chimpanzees (n = 16), gorillas (n = 16) and orangutans (n = 11). Ontogenetic changes in fibular/tibial strength were also analyzed due to KNM-WT 15000's juvenile status. Cross-sectional properties at midshaft were derived from multi-plane radiography and external contours, or CT scanning. Comparisons of log-transformed fibular/tibial polar second moment of area and anteroposterior (A-P) and mediolateral (M-L) second moments of area were carried out between extant species. Fossil deviations from each extant taxon's mean proportion were calculated in standard deviation (SD) units for that taxon. Great apes differ significantly from modern humans, with relatively stronger fibulae, particularly in the M-L plane. KNM-WT 15000 is more than 2 SD from all great apes (≥3 SD in the M-L plane) and within 1 SD of modern humans for almost all variables. This is not a result of its age, as fibular/tibial strength slightly decreases with age (i.e., becomes less like that of great apes) in humans. OH 35 falls within 1 SD of chimpanzees and orangutans for the majority of cross-sectional proportions, but more than 1 SD from humans. KNM-WT 15000 is demonstrated to be fully modern, complimenting other indications of complete terrestrial bipedality and possibly showing adaptations for endurance running. OH 35 has some human-like features; however, the relative strength of the two bones aligns the specimen with great apes, consistent with a significant degree of arboreality, in particular, vertical climbing.